2019
DOI: 10.1016/j.psychres.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of sleep disorder symptoms in psychiatric disorders

Abstract: Difficulty falling asleep or maintaining sleep, poor sleep quality, nightmares, and excessive daytime sleepiness are some of the key clinical symptoms of sleep disturbances observed among individuals with psychiatric illnesses. This study aimed to determine the prevalence of symptoms of sleep disorders including parasomnia, narcolepsy, obstructive sleep apnea, circadian rhythm disorder and restless leg syndrome/periodic limb movement (RLS/PLMS) and its correlates in patients with psychiatric diagnoses. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
4
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 51 publications
2
51
4
5
Order By: Relevance
“…This implies that sleep disorders are a common feature of psychiatric disorders. It is similar to findings by other researchers such as Homiball et al [56] who reported 40.75%. The finding also hints at a possibly strong link between sleep problems and psychiatric disorder, which has been studied by many [29,57].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This implies that sleep disorders are a common feature of psychiatric disorders. It is similar to findings by other researchers such as Homiball et al [56] who reported 40.75%. The finding also hints at a possibly strong link between sleep problems and psychiatric disorder, which has been studied by many [29,57].…”
Section: Discussionsupporting
confidence: 92%
“…The 6.0 % prevalence of narcolepsy is higher than the range reported by Longstreth et al which put it at 0.025%-0.05% [21] Prevalence of narcolepsy in recent years has varied with regions of the world studied and methodology as has been the case with other sleep disorders. Homiball [56] who reported 12.5% prevalence for narcolepsy symptoms compared to 10.9% in our study. This is higher than the 6.0% we found for narcolepsy disorder.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Sleep disturbances, including hypersomnia, insomnia, or irregular sleep patterns, result in various cognitive impairments and mood disorders (1,2). Prolonged sleep deprivation or chronic sleep abnormalities are risk factors for the major depressive disorder (MDD) (3) and bipolar disorder (BD) (4), whereas disturbed sleep appears as a key symptom of mental diturbances (5, 6). Mechanisms connecting sleep deprivation and mood disorders remain, however, unclear.…”
mentioning
confidence: 99%
“…disorders self-report symptoms of a sleep disorder (Hombali et al, 2018). A recent systematic review of sleep disorders in early psychosis has suggested that sleep disturbances may be associated with symptom severity and elevated rates of both help-seeking and suicidality (Davies, Haddock, Yung, Mulligan, & Kyle, 2017).…”
mentioning
confidence: 99%